APLIKASI SISTEM UJIAN MASUK PENERIMAAN MAHASISWA BARU BERBASIS WEB MENGGUNAKAN PHP DI STMIK PPKIA PRADNYA PARAMITA MALANG - Mumpuni, Indah Dwi; Wijayanti, Fitria Ari (DINAMIKA DOTCOM, 2011)
STMIK Pradnya Paramita Malang is a growing campus and over time students who enroll each year is increasing. Entrance examination for admission on campus is still using manual file that is paper. So many weaknesses, in addition to the validation process takes a long time values are also many things that cause the file is not safe. The application system created aims to simplify the assessment process for admission exam results in STMIK Pradnya Paramita Malang, fast and accurate. Applications entrance examination system for admission based on web using PHP in STMIK Pradnya Paramita Malang to simplify the working committee and the process of validation test results fast and accurate so that STMIK Pradnya Paramita campus Malang become a developed and advanced.Keywords: Application System, Entrance Exams Admissions, STMIK PPKIA Pradnya ParamitaÂ  Malang